ACE Project—Advocating for Clinical Excellence: Creating Change in the Delivery of Palliative Care. (August 2013) - Otis-Green, Shirley; Yang, Eunice; Lynne, Lisa
Background: Psychologists, social workers, and spiritual care professionals report inadequate preparation to maximize their effectiveness in advocating for institutional reform to meet oncology patients' diverse bio-psychosocial-spiritual and cultural needs. This article provides an overview of the ACE Project, a National Cancer Institute, 5 year, R25-funded transdisciplinary palliative care education program designed to enhance the advocacy and leadership skills of 301 competitively selected psycho-oncology professionals. Methods: ACE Project participants identified an institutional goal, refined their goals during the course and received mentorship and support throughout the subsequent year. Participants were invited to return to a Reunion Conference in year five to report on their activities, network, and share the results of their change efforts. A subset of 28 ACE Project participants contributed to this OMEGA special issue. Results: Participants' goals primarily focused on strategies to improve clinical care through program development and improvements in palliative care education within their institutions. Conclusions: The results of this transdisciplinary leadership skills-building program for psycho-oncology professionals affirm the feasibility and perceived need for the program. See the ACE Project website (http://www.cityofhope.org/education/health-professional-education/nursing-education/ACE-project/Pages/default.aspx ) for additional program information.